2004
DOI: 10.2165/00126839-200405010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Volume Efficacy and Reduced Influence on Measures of Coagulation Using Hydroxyethyl Starch 130/0.4 (6%) with an Optimised in???Vivo???Molecular Weight in Orthopaedic Surgery

Abstract: HES 130/0.4 and HES 200/0.5 were found to be similar with regard to volume efficacy. Sensitive coagulation parameters returned more rapidly to normal in the HES 130/0.4 group. Lower in vivo molecular weight and more rapid excretion of HES 130/0.4 are the likely explanations for the smaller influence on coagulation in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 18 publications
4
70
0
1
Order By: Relevance
“…The hemodilution effect of HES 130/0.4 associated with its mode of action was reflected by significant changes in hematological and coagulation parameters. The quick recovery of Factor VIII and vWF in adults after surgery is in line with other findings [3,11,12]. However, it is not possible to separate the effects of profound bleeding from those attributable to hemodilution in an uncontrolled trial.…”
Section: In Patients Undergoingsupporting
confidence: 77%
See 1 more Smart Citation
“…The hemodilution effect of HES 130/0.4 associated with its mode of action was reflected by significant changes in hematological and coagulation parameters. The quick recovery of Factor VIII and vWF in adults after surgery is in line with other findings [3,11,12]. However, it is not possible to separate the effects of profound bleeding from those attributable to hemodilution in an uncontrolled trial.…”
Section: In Patients Undergoingsupporting
confidence: 77%
“…This advancement leads to a more rapid metabolization and degradation of HES molecules and thus to a minimal plasma accumulation even after repeated administration of HES 130/0.4 [2]. In addition, the influence on the coagulation system has been minimized [3]. Several studies confirmed that HES 130/0.4 does not result in deterioration in kidney function [4] in surgery even in those patients who are prone to acute renal failure [5].…”
Section: Introductionmentioning
confidence: 99%
“…For hydroxyethyl starches, these effects appear closely related to the intrinsic properties of the different starch solutions, such as a high in vitro molecular weight and a high degree of hydroxyethyl substitution. 48,49 Although some plasma substitute used in the context of ANH may directly interfere with normal hemostasis, there is no evidence from the literature that ANH is associated with increased preoperative bleeding. In a first meta-analysis evaluating the efficacy of ANH in reducing perioperative allogeneic transfusion, Bryson et al 50 reported that ANH had a small and insignificant effect on the volume of blood lost in the perioperative period (weighted mean difference: -117 mL; 95% CI, -292 to 58 mL).…”
Section: Anh and Hemostasismentioning
confidence: 99%
“…In general, an HES solution with low molecular weight (MW) and low degree of substitution (DS) is preferred because HES solution with high MW and high DS is harder to metabolise or eliminate and thus has a prolonged adverse effect on coagulation [2,[6][7][8][9][10][11][12]. Recently, several studies of balanced salt-based HES solution with high MW and high DS (670 ⁄ 0.75; referred to as bhHES hereafter) have reported beneficial effects on coagulation [13][14][15].…”
mentioning
confidence: 99%